Procedural safeguards under the European convention on human rights in public (administrative) law matters - Tina Sever (DANUBE: Law, Economics and Social Issues Review, 2018)
The effectiveness of procedure is important for parties (e.g. citizens or business entities) to be able to exercise their rights in due time and is a key foundation of the rule of law. A State with an effective legal system provides a business-friendly environment, which is appealing for investments. The State decides on permits, licenses, taxes, etc. by applying administrative procedure. The aim of the paper is to identify and analyse such matters under public (administrative) law at the national level, which - due to their influence on private rights or obligations - fall under the civil or criminal limb of Article 6 of the ECHR and its requirements, as well as the requirements of Article 13. By means of a case study and descriptive-analytical and normative methods, the paper identifies comparatively selected cases and analyses the ECtHR test regarding reasonable time, focusing on overall procedure duration and the awarded compensations. The findings show that the ECtHR does not define reasonable time in abstracto. Therefore, the established violations among the states range from two-year procedures to nine years and more, depending on the circumstances of each individual case. Similarly, there are also variations in terms of compensation awarded.
Keywords: 330; Administrative Matters; ECtHR Case Law; Legal Remedy; Just Satisfaction; Reasonable Time; Procedure Effectiveness